Difference of Clotting Time and Bleeding Time in the ABO Blood Groups - Munazza Khan, Zafaruddin, Noor Ul Haq, Saba Farooq, Fareeha Hasan, (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Blood group, clotting time (CT) and bleeding time (BT) are vital haematological parameters that are tested prior to any surgery. Blood groups are associated with various diseases and blood group "O" linked with nose bleeds. The aim of this study is to evaluate the association between CT and BT between various blood groups and to find differences in gender among these parameters. Study Design: A cross-sectional observational study. Place and Duration: In the department of Physiology and Medicine, MTI LRH, Peshawar Pakistan for one-year duration from March 2021 to February 2022. Methods: This study was held amongst the 200 healthy individuals. The agglutination method is used for blood grouping, capillary tube method for CT and Dukes method for BT. Mean clotting and bleeding times (in seconds) were compared. Results: The study was conducted among 200 individuals (120 men, 80 women) aged 20-25 years. Although the changes were not statistically significant, the values ​​of CT and BT were higher in blood group O, less BT in type B and AB blood grouping had lowest CT (p> 0.17). Women had greater CT and BT values ​​than men (p values ​​<0.001). There was also a significant association between the clotting time and bleeding time (Pearson's correlation coefficient, p = 0.512, p <0.001). Conclusion: The conducted analysis showed a propensity to a greater jeopardy of haemorrhagic conditions and a lesser risk of thrombotic events in ‘’O’’ blood group in comparison to groups AB, A or B. A multicentre, bigger population study with an importance on determining plasma vWF levels may be useful for confirming results, identifying risk groups and taking preventive measures early. Keywords: Bleeding time (BT), ABO blood group, von Willebrand factor (vWF) and Clotting time (CT).